A combined FEM and three-dimensional asymptotic solution based analysis on stress concentration/intensity around elliptical/circular cylinder shaped surface flaws in stretched plates - Chaudhuri, Reaz A. (Applied mathematical modelling, 2015)
C0-type triangular “layered” plate elements, formulated on the assumptions of transverse inextensibility and layer-wise constant shear-angle theory (LCST) are employed to investigate the weakening effects of localized elliptical (circular being a special case) cylindrical surface flaws in isotropic plates. Numerical results indicate severe transverse shear deformation in the vicinity of a surface flaw boundary. In addition, a recently developed asymptotic solution to the problem pertaining to the stress fields in the neighborhood of the circumferential corner line or line of intersection of a circular cylindrical external part-through open hole and an interior surface of an isotropic plate, subjected to far-field extension (mode I), in-plane shear (mode II) loadings, is presented. Most importantly, the effects of stress singularity in the neighborhood of the circumferential re-entrant corner lines of the elliptical/circular cylindrical surface flaws, weakening plates, are numerically assessed, because of their role in crack initiation.